2017
DOI: 10.1002/cne.24276
|View full text |Cite
|
Sign up to set email alerts
|

Parvalbumin‐expressing ependymal cells in rostral lateral ventricle wall adhesions contribute to aging‐related ventricle stenosis in mice

Abstract: Aging-associated ependymal-cell pathologies can manifest as ventricular gliosis, ventricle enlargement, or ventricle stenosis. Ventricle stenosis and fusion of the lateral ventricle (LV) walls is associated with a massive decline of the proliferative capacities of the stem cell niche in the affected subventricular zone (SVZ) in aging mice. We examined the brains of adult C57BL/6 mice and found that ependymal cells located in the adhesions of the medial and lateral walls of the rostral LVs upregulated parvalbum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…The specificity of the guinea-pig anti-S100β antibody 287004 was tested by the provider (Synaptic Systems) using immunocytochemistry and western blots on cells transfected with the S100β sequence and on brain slices. Its specificity was further confirmed using western blot analysis (Filice et al 2017). The staining obtained in brain sections was reported to be similar to that obtained with another antibody directed against S100β raised in rabbit (Filice et al 2017).…”
Section: /79supporting
confidence: 63%
See 1 more Smart Citation
“…The specificity of the guinea-pig anti-S100β antibody 287004 was tested by the provider (Synaptic Systems) using immunocytochemistry and western blots on cells transfected with the S100β sequence and on brain slices. Its specificity was further confirmed using western blot analysis (Filice et al 2017). The staining obtained in brain sections was reported to be similar to that obtained with another antibody directed against S100β raised in rabbit (Filice et al 2017).…”
Section: /79supporting
confidence: 63%
“…Its specificity was further confirmed using western blot analysis (Filice et al 2017). The staining obtained in brain sections was reported to be similar to that obtained with another antibody directed against S100β raised in rabbit (Filice et al 2017). The specificity of the goat anti-GFP antibody AB5450 was tested by the provider (Abcam) using immunoprecipitation and immunocytochemistry on transfected cells and on brain slices.…”
Section: /79mentioning
confidence: 60%
“…Loading was controlled using Ponceau S staining and membranes were blocked with 5% milk in 0.1% Tween 20 in TBS for 1 h at room temperature and incubated overnight at 4 °C with rabbit polyclonal antibody PV-25 (Swant, Marly, Switzerland) at 1:5,000, or mouse monoclonal COX I antibody (ThermoFisher, Switzerland) at 1:1,000, respectively. The PV-25 antibody has been validated for Western blot analysis in our previous study 20 . Horseradish peroxidase (HRP)-conjugated goat anti-rabbit antibody or goat anti-mouse antibody (Sigma-Aldrich, Buchs, Switzerland) were added at a dilution of 1:10,000 for 2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…However, following brain injury we observed upregulation of PV in ependymal cells and reactive astrocytes. Ependymal cells react with prompt and persistent PV-upregulation to invasive injury inflicted onto the lateral ventricle wall 19 and in aging-related lateral ventricle wall stenosis 20 . We demonstrated that injury-induced PV overexpression in ependymal cells was dependent on NF-κB signaling and was modulated by altering the level of oxidative stress, which implicates inflammation induced by injury in this process.…”
Section: Introductionmentioning
confidence: 99%
“…In mutant brains, however, the regions lacking S100  ependymal cells were increased . We also used another marker, parvalbumin (PV), which is specifically expressed in ependymal cells at the stenosed region (Filice et al, 2017), and found that PV-positive cells were increased in mutant brains ( Figures S2A and S2B), confirming the enhanced stenosis in mutant brains. These results indicate that CAMSAP3 mutation promotes ventricular stenosis or fusion at the boundaries between the striatum and septum.…”
Section: Increased Ventricle Stenosis and Fusion In Camsap3 Mutant Brmentioning
confidence: 64%